Pengaruh Profitabilitas dan Likuiditas Terhadap Zakat Perusahaan Pada Bank Umum Syariah di Indonesia - Bela, Nur Evita; Fahlevi, Rizal; Putra, Purnama; Khoiriyah, Ummi (STIE Indonesia Banking School, 2024)
This research aims to determine the influence of profitability and liquidity on corporate zakat (Islamic almsgiving) for Islamic Commercial Banks in the period of 2021-2023 in Indonesia. The population of this study consists of Islamic Commercial Banks operating in Indonesia. The research employs purposive sampling as the sampling method. After selection, the sample includes four Islamic Commercial Banks: Bank Muamalat Indonesia, Bank Syariah Indonesia, Bank Mega Syariah, and Bank Panin Dubai Syariah. This research follows a quantitative approach using multiple regression analysis, and the analysis is conducted using SPSS. The research results indicate that the profitability variables, proxied by Return On Equity (ROE) and the Operating Expenses to Operating Income Ratio (BOPO), and the liquidity variable, proxied by Financing to Deposit Ratio (FDR), collectively have a positive and significant impact on corporate zakat. In partial testing, the Profitability variable, which is proxied by Return On Equity (ROE), has a significant positive influence on the company's zakat expenditure, while the Operating Costs, Operating Income (BOPO) has no effect on the company's zakat expenditure, and the Liquidity variable, which is proxied by the Financing to Deposit Ratio. (FDR) has a significant negative effect on company zakat expenditure. This explains how the profitability and liquidity of Islamic banks can affect their social obligations in paying corporate zakat, which is an important aspect of the Islamic economy in Indonesia.